Branding like a City: Barcelona and its Literature at the Buenos Aires Book Fair - García Naharro, Fernando (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
This essay seeks a detailed and intimate understanding of the presence of Barcelona as Guest of Honour at the 45th Buenos Aires Book Fair. In so doing, I focus on the stand of Barcelona at the Buenos Aires Book Fair for arguing that exhibition units create the conditions for telling particular stories about national/local literatures to a broad and foreign audience. Moreover, building bridges between existing lines of research and informed by ongoing debates in the field, this paper aims to highlight the entanglements between politics and tourism, “pure” literature and marketplace imperatives. Everything analysed, however, through cultural products and exhibition spaces.